Effects of probiotic-containing products on stool frequency and intestinal transit in constipated adults: systematic review and meta-analysis of randomized controlled trials - Miller, Larry E. (Annals of gastroenterology, 2017)
Probiotics are commonly recommended for the alleviation of constipation symptoms. The aim of this research was to determine the effects of probiotic-containing products on stool frequency and intestinal transit time (ITT) in constipated adults and to determine the factors that influence the efficacy of these products. We conducted a systematic review of randomized controlled trials that measured weekly stool frequency or ITT in constipated adults receiving probiotic-containing supplements. A random effects meta-analysis was performed; stool frequency was summarized by the mean difference statistic and ITT was summarized by the standardized mean difference (SMD) statistic. Meta-regression and diagnostic model performance testing were used to identify publication bias and sources of heterogeneity. A total of 21 studies (23 comparisons) comprising 2656 subjects were included. All studies utilized probiotics containing or species. Probiotic-containing products resulted in a mean increase in weekly stool frequency of 0.83 (95% confidence interval [CI] 0.53-1.14, P<0.001). There was high heterogeneity among the studies ( =85%, P<0.001) and evidence of significant publication bias (Egger's P-value <0.01). After adjustment for publication bias, the mean difference in weekly stool frequency was reduced from 0.83 to 0.30. The effects on stool frequency were greater in studies where functional constipation was diagnosed using Rome III (P<0.01), or Rome II or III criteria (P<0.05), compared to non-Rome diagnosis techniques. Probiotic-containing products were also efficacious in reducing ITT (SMD=0.65, 95%CI 0.33-0.97, P<0.001). There was high heterogeneity among studies ( =66%, P<0.01), but no evidence of publication bias (Egger's P-value=0.52). A larger total sample size was associated with greater efficacy as regards ITT (P=0.03). The probiotic species, the number of probiotic strains and the daily probiotic dosage had no influence on the outcomes. Supplementation with products containing or species increases stool frequency and reduces ITT in constipated adults. However, since significant heterogeneity in outcomes was detected among the studies analyzed, the results should be interpreted with caution.